Analisis Hubungan Pengetahuan tentang Deteksi Dini Kanker Payudara pada Remaja Putri melalui Pemeriksaan Payudara Klinis (SADANIS) - Tempali, Sri Restu (Jurnal Bidan Cerdas, 2019)
Fibroadenoma is the most benign breast neoplasm. These tumors grow in young women with the highest frequency in young women 21-25 years, with a prevalence of more than 9% of the female population affected by fibroadenoma. Breast cancer still has a high likelihood of being cured when it comes to early or early. Early detection of breast cancer is an examination program to recognize breast cancer while still small, and before cancer has a chance to spread. One of the early detection efforts is clinical breast examination (SADANIS) which is carried out at least once every 3 years or if abnormalities are found in the process of self-breast examination (BSE) and carried out by trained health workers. The purpose of the study was to determine the relationship between knowledge and early detection of breast cancer risk in young women through the SADANIS examination. Observational research method with a cross-sectional approach. The sample is a student of SMK 1 Palu and a student of AKBID Cendrawasih Palu. The results showed that there was a significant relationship between knowledge about the SADANIS examination and the practice of SADANIS examination in young women so there is a strong relationship between young women's knowledge BSE in early detection of breast cancer as evidenced by the p-value 0.007<Î± (0.05). The conclusion is that the knowledge of young women about sadanis examination is still low.